Chicken as inquisitive meaning reference for carefulness, uselessness and betrayal in Malay proverbs [Ayam sebagai rujukan makna inkuisitif berhati-hati, sia-sia dan khianat dalam peribahasa Melayu] - Daud, Muhammad Zaid; Subet, Mary Fatimah (Penerbit Universiti Sains Malaysia, 2022)
Malay proverbs which are sourced from chicken, are 90 in total. Various references of chicken have been created by the Malays to mirror the behaviours and actions of human beings implicitly. Each of the references can provide lessons, advices and reprimands in a gentle manner and can still be used up to today. The attributes of “careful”, “useless” and “betrayal” are among these references. In order to analyse the data of these proverbs, the research will use the Inquisitive Semantics Approach, besides the application of bridging cross reference (BCR) based on the corpus data obtained from Pangkalan Korpus Dewan Bahasa dan Pustaka (DBP) and Malay Concordance Project (MCP). Therefore, as the objective of this study, the researchers will explore the reasons why the Malay community choose the imagery of chicken. Each of these references will benefit the authentic data which are related to the cognition, culture and intellect of the Malay community in itself. This research employs fully qualitative approaches through documentary analysis that involves the Malay proverb data which have been recorded beforehand. The findings of these proverbs data are collected from Kamus Peribahasa Melayu Edisi Kelima, Kamus Istimewa Peribahasa Melayu Edisi Kedua and Kamus Peribahasa Melayu using the purposive sampling method. In conclusion, this study finds that the inquisitive semantics approach is capable of uncovering the Malay proverbs’ meanings which are not confined only to literal and cognitive understandings but reflect also the height of intellect and philosophy of the Malays themselves.